The inter-relationship between p53, survivin and XIAP in colorectal cancer cells response to apoptotic stimuli - Atakpa, Isaac (2024)
Colorectal cancer (CRC) also known as colon cancer usually starts in the inner lining of the colon, grows as a non-cancerous polyp and then develops into an adenoma after several years. Overexpression of two inhibitor of apoptosis (IAP) proteins, XIAP and survivin is prevalent in cancers including CRC. Under hypoxia, these cells exhibit even greater resistance to apoptosis due to the expression of HIF-1α, a transcriptional activator of survivin and many other proteins. The increased expression of survivin and XIAP has been associated with chemotherapeutic resistance in hypoxic conditions. P53, a sensor of genotoxic stress and an initiator of apoptosis, is a tumour suppressor protein that regulates transcription of apoptosis genes. This thesis aims to understand the inter-relationship between p53, survivin and XIAP in colorectal cancer cells response to apoptotic stimuli. Using colorectal cancer cells with specific stable knockouts of p53 and XIAP, in conjunction with quantitative real-time PCR and western blotting, the presented data show that survivin was repressed at both the transcriptional and post-translational levels in HCT 116 p53+/+ and XIAP-/- cells, which exhibited high expression of p53 protein. Whereas in p53 -/- cells, survivin mRNA and protein levels were highly expressed. In contrast, no difference was observed in either gene or protein expression levels of XIAP in the p53+/+ and p53-/- cells. Thus, p53 represses survivin independent of XIAP. However, p53 does not repress XIAP. Furthermore, the role of survivin in apoptosis inhibition in these cells was investigated in normoxia and hypoxia. The hypothesis that survivin inhibition of apoptosis was dependent on XIAP/or p53 was tested. Using apoptotic stimuli TRAIL and etoposide flow cytometry analysis of caspase3/7 activity revealed that in TRAIL-mediated apoptosis, survivin functions independently of XIAP, while in the etoposide-induced cell death, the role of survivin was XIAP dependent. Moreover, TRAIL- mediated apoptosis was independent of p53 while etoposide-induced cell death was p53 dependent. The effect of a small molecule, YM 155, which has been described as an inhibitor of survivin was examined in several cancer lines. Quantitative real-time PCR and western blotting analysis showed that survivin was only repressed at the transcriptional level in U2OS cells. Whereas, post-translational elimination of survivin was seen in all the cell types. Interestingly, we unveiled a novel link between YM155 and survivin degradation via the autophagy-lysosomal pathway. In addition, flow cytometry analysis showed the cytotoxic effect of YM 155 was reduced under hypoxia. This thesis shows that p53 repression of survivin is XIAP independent. The role of survivin in apoptosis inhibition is XIAP dependent, but this dependency varies depending on the pathway of cell death. YM 155 reduces survivin via different mechanism of actions.